Inhibition of intracellular proton-sensitive Ca2+-permeable TRPV3 channels protects against ischemic brain injury - Xiaoling Chen; Jingliang Zhang; KeWei Wang (Elsevier, 2022)
Ischemic brain stroke is pathologically characterized by tissue acidosis, sustained calcium entry and progressive cell death. Previous studies focusing on antagonizing N-methyl-d-aspartate (NMDA) receptors have failed to translate any clinical benefits, suggesting a non-NMDA mechanism involved in the sustained injury after stroke. Here, we report that inhibition of intracellular proton-sensitive Ca2+-permeable transient receptor potential vanilloid 3 (TRPV3) channel protects against cerebral ischemia/reperfusion (I/R) injury. TRPV3 expression is upregulated in mice subjected to cerebral I/R injury. Silencing of TRPV3 reduces intrinsic neuronal excitability, excitatory synaptic transmissions, and also attenuates cerebral I/R injury in mouse model of transient middle cerebral artery occlusion (tMCAO). Conversely, overexpressing or re-expressing TRPV3 increases neuronal excitability, excitatory synaptic transmissions and aggravates cerebral I/R injury. Furthermore, specific inhibition of TRPV3 by natural forsythoside B decreases neural excitability and attenuates cerebral I/R injury. Taken together, our findings for the first time reveal a causative role of neuronal TRPV3 channel in progressive cell death after stroke, and blocking overactive TRPV3 channel may provide therapeutic potential for ischemic brain injury.